Pengaruh Core Self-Evaluation dan Literasi Ekonomi Terhadap Minat Berwirausaha di SMK Batik 1 Surakarta Tahun Pelajaran 2019/2020 - Frela Wahyu Dewanti; Baedhowi Baedhowi; Leny Noviani (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2019)
is research aims to determine (1) influence between core selfevaluation and economic literacy on interest in entrepreneurship; (2) influence between core self-evaluation on interest in entrepreneurship; (3) influence between economic literacy on interest in entrepreneurship. The research methods used in this study is a descriptive quantitative research method. The population in this research was student of Management and Business Expertise SMK Batik 1 Surakarta with a total of 147 students. The research sample of 108 students with proportional sampling. Data collection techniques carried out by questionnaire, test, and documentation techniques. Data analysis techniques using Multiple Regression Analysis with the help of SPSS version 25. The results showed (1) core self-evaluation and economic literacy simultaneously have positive effect on entrepreneurial interests; (2) core self-evaluation have positive effect on entrepreneurial interests; (3) economic literacy have positive effect on entrepreneurial interests.